The cloxacillin for mastitis treatment. Laboratory trials - ΑΝΥΦΑΝΤΑΚΗΣ, ΕΜΜΑΝΟΥΗΛ (Journal of the Hellenic Veterinary Medical Society, 2019)
After a brief review of literature on this subject, information is given about the methods used in the laboratory to detect the effect of cloxacillin on a culture of staphylococcus auieus, strain 37 J 67, in cow's sterilized separated milk at 37°C, during the log, stationary and decline phases. The stability of cloxacillin in milk and culture of staphylococcus aureus 37167 was also investigated. It became clear that cloxacillin has a bactericidal effect on the fast growing cells of the Staph, aureus. The effect of the cloxacillin on cultuies being at stationary or decline phases, appears to be much lower than at the log phase. Cloxacillin was shown to be stable in milk and the cultures of the microorganism in question, at 37°C, and even more in the case of milk alone.